Analisis Pendapatan Usahatani Kakao Non Sambung-samping dan Kakao Sambungsamping di Tamalea Kecamatan Bonehau Kabupaten Mamuju - Andriyani, Lusy; Kaimuddin; Dahniar (Program Studi Kehutanan Fakultas Pertanian dan Kehutanan Universitas Sulawesi Barat, 2022)
Cocoa production in recent years has experienced a very rapid decline, where in previous years cocoa production usually reached 1-2 quintals per month. However, unlike today, the income earned is lower than the previous one, so some farming communities turn to the side-connected technique. This study aims to determine how the level of farmer's income is the feasibility of farming and the value of BEP (Break Even Point) who have not done side-grafting and who have done side-grafting on cocoa plants. Data collection methods used in this study were observation, interviews, and documentation. Based on the results of research conducted in Tamalea Village, Bonehau District, Mamuju Regency, it shows that the income from side-connected cocoa farming is smaller than the income from side-connected cocoa farming. By looking at the income results of non-side grafting cocoa farming, which is Rp. 177,427,844/22.5 ha or Rp. 7,885,681,9/ha and the income of side-connected cocoa farming is Rp. 380,322,075/23 ha or Rp. 16,535,742.4/ha. The results of the R/C ratio of non-side grafting cocoa farming are smaller than the R/C ratio of side-coating cocoa farming. Non-side-connecting cocoa farming is feasible by looking at the R/C ratio value of 2.47, which means that each expenditure is Rp. 100,- will get an income of 247, and sidegrafting cocoa farming is feasible by looking at the R/C ratio value of 3.09, which means that each expenditure is Rp. 100,- will get an acceptance of 309,-. The results of BEP (Break Even Point) or the breakeven point of non-cross-linked and side-linked cocoa farming are non-side-connected cocoa farming with a volume BEP value of 5,476.825 kg and a BEP price of Rp. 8,892.262/kg, while side-by-side cocoa farming with a volume BEP value of 8,267,178 kg and a BEP price of Rp. 7,104,606/kg.